Temporal proteomic profiling reveals functional pathways in vaccinia virus-induced cell migration - Lu, Jiayin; Liu, Wei; Chen, Xue-Zhu; Wang, Yiwen; Ying, Tianlei; Qiao, Liang; Liu, Yan-Jun; Liu, Baohong (Frontiers in Microbiology, 2023)
Viral diseases have always been intricate and persistent issues throughout the world and lack of holistic discoveries of molecular dysregulations of virus-host interactions. The temporal proteomics strategy can identify various differentially expressed proteins and offer collaborated interaction networks under pathological conditions. Herein, temporal proteomics at various hours post infection of Vero cells were launched to uncover molecular alternations during vaccinia virus (VACV)-induced cell migration. Different stages of infection were included to differentiate gene ontologies and critical pathways at specific time points of infection. The enrichment of functional interaction networks and pathways verified the significances of regulation of actin cytoskeleton and lamellipodia during VACV-induced fast cell motility. Current results offer the systematic proteomic profiling of molecular dysregulations at different stages of VACV infection and potential biomedical targets for treating viral diseases.